HMGB1 is secreted by 3T3‐L1 adipocytes through JNK signaling and the secretion is partially inhibited by adiponectin. Issue 9 (19th July 2016) - Shimizu, Toshiaki; Yamakuchi, Munekazu; Biswas, Kamal Krishna; Aryal, Bibek; Yamada, Shingo; Hashiguchi, Teruto; Maruyama, Ikuro
Abstract : Objective: Obesity is a chronic inflammatory disease, and adipocytes contribute to obesity‐associated inflammation by releasing inflammatory mediators. High mobility group box 1 (HMGB1), a highly conserved DNA‐binding protein, mainly localized to cell nuclei, has been recently recognized as an innate pro‐inflammatory mediator when released extracellularly. It was hypothesized that HMGB1 is an adipocytokine that acts as an innate pro‐inflammatory mediator in white adipose tissue (WAT) of patients with obesity and is associated with insulin resistance. Additionally, it was hypothesized that HMGB1 secretion is regulated by adiponectin. Methods: 3T3‐L1 cells were differentiated into mature adipocytes. After tumor necrosis factor‐α (TNF‐α) stimulation, HMGB1 in culture media was measured. Localizations of HMGB1 in 3T3‐L1 adipocytes and human WAT were examined by immunostaining. Results: HMGB1 was secreted from TNF‐α‐induced 3T3‐L1 adipocytes through JNK signaling. HMGB1‐activated MAP kinases (ERK1/2, JNK) and suppressed insulin‐stimulated Akt phosphorylation in 3T3‐L1 adipocytes. The cytoplasm in 3T3‐L1 adipocytes and adipocytes of WAT from a patient with obesity was intensely stained with HMGB1. Adiponectin partially inhibited TNF‐α‐induced HMGB1 secretion from 3T3‐L1 adipocytes. Conclusions: These findings suggest that HMGB1 is a pro‐inflammatory adipocytokine involved in WAT inflammation and insulin resistance in patients with obesity, which may contribute to the progression of metabolic syndrome, and that adiponectin protects against HMGB1‐induced adipose tissue inflammation.